In situ characterisation of nanoscale electromechanical properties of quasi-two-dimensional MoS2 and MoO3, arXiv preprint arXiv - Walia, Sumeet; Nili, Hussein; Balendhran, Sivacarendran; Late, Dattatray J.; Sriram, Sharath; Bhaskaran, Madhu (Condensed Matter Materials Science, 2014)
Precise manipulation of electronic band structures of two-dimensional (2D) transition metal dichalcogenides and oxides (TMD&Os) via localised strain engineering is an exciting avenue for exploiting their unique characteristics for electronics, optoelectronics, and nanoelectromechanical systems (NEMS) applications. This work experimentally demonstrates that mechanically-induced electrical transitions can be engineered in quasi-2D molybdenum disulphide (MoS2) and molybdenum trioxide (MoO3) using an in situ electrical nanoindentation technique. It is shown that localised strains on such quasi-2D layers can induce carrier transport alterations, thereby changing their electrical conduction behaviour. Such strain effects offer a potential tool for precisely manipulating the electronic transport properties of 2D TMD&Os, and understanding the interactions of the atomic electronic states in such layered materials.

Impedimetric humidity sensor based on ?-Fe2O3 nanoparticles - Patil, U. V.; Rout, C. S.; Late, Dattatray J. (Advanced Device Materials, 2015)
Humidity sensing characteristics of thick-film sensors based on α-Fe2O3 nanoparticles synthesized by hydrothermal method have been reported. The as-synthesized α-Fe2O3 nanoparticles were characterized by using XRD, Raman spectroscopy, TEM and HRTEM. Our TEM result depicts that the size of α-Fe2O3 nanoparticles were in the range of 20–30 nm with highly crystalline nature. For humidity sensing experiment, the sensitivity of our α-Fe2O3 nanoparticles-based sensor device was found to be ∼99% and the fastest response times were noted, which indicate that the α-Fe2O3 nanoparticle-based humidity sensor device has more future prospects and demand. The humidity sensing properties of α-Fe2O3 nanoparticles seem to be associated to the sorption sites for the water molecules at the nanoparticles interfaces.

In situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Improved nonenzymatic glucose sensing properties of Pd/MnO2 nanosheets: synthesis by facile microwave-assisted route and theoretical insight from quantum simulations - Ponnusamy, Rajeswari; Gangan, Abhijeet; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Physical Chemistry B, 2018)
The electrocatalytic properties of manganese oxide (MnO2) can be improved significantly by making hybrids/composites with noble metals (Au, Pd). Here, efforts have been made to synthesize the MnO2/Au and MnO2/Pd nanocomposites by a facile, rapid microwave irradiation method. The products characterized by X-ray diffraction and transmission electron microscopy exhibited their tetragonal phase and nanosheet morphology. The efficiency of the prepared composite materials as glucose sensor was tested by cyclic voltammetry and chronoamperometry measurements, and the results are discussed. The study revealed that successful modification of MnO2 by Pd led to excellent sensing performance by the reduction of size and the synergistic effect between MnO2 and PdO, which expedites the electron transfer. Besides, the wide detection range, good selectivity, and stability demonstrate its robustness in the design of electrochemical sensor platform. To get theoretical insight into the excellent sensing performance of MnO2/Pd, we have performed detailed density functional theory simulations to explore the charge transfer and bonding mechanism of glucose on MnO2 and Pd/Au-doped MnO2 surface. Pd is bonded strongly on MnO2 and makes MnO2/Pd more conducting due to the enhancement of density of states near Fermi level. The higher binding energy of glucose and enhanced charge transfer from glucose to Pd-doped MnO2 compared to bare MnO2 infer that Pd-doped MnO2 possess superior charge-transfer kinetics, resulting in higher glucose sensing performance, which supports our experimental observations.

Introduction - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
The book provides comprehensive and updated research contribution about advances in synthesis/growth of 2D materials for various sensor applications, their working principles, and mechanism behind the sensor as well physics and chemistry of materials.

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors